Information Literacy, technological impact and its impact on learning for Life - Nuñez Benitez, Andrea Susana (2014)
The aim of this research seeks to address from an overview of the importance of acquiring skills and informational skills in this new era of knowledge, making a brief tour of the history of reading and writing to the appearance of the internet, then go defining using your term (information literacy, information literacy) or designations. In addition to establishing a brief discussion on the influence of the mixture or meeting of different generations in relation to their behavior regarding the use of the information. Likewise the value of the acquisition of information skills indicating some experiences of research and proposals that establish certain ideas about the best way to meet the challenge of inserting technology into our lives especially in education mentioned. Ending are some simple descriptions of the impact of information literacy in lifelong learning, inspired by the declaration of Alexandria and considering its impact on cultural educational, social, political, economic and citizens.